Desenvolvimento Participativo: uma sugestão de reformulação conceptual - António Fragoso (Universidade do Minho, 2005)
The focus of the paper lies in a first moment on the several concepts of territorial development, to sketch an overview of its emergence and evolution. A particular emphasis is given to community development and local development, followed by a brief approach on community action and community organisation. We try to show that these are different conceptual notions, although it is common to mix them up. On the other hand there is a complex network of intertwining issues dressing such concepts, which makes the result unsatisfactory. That being the case and even if several semantic problems have always been felt in the field of development, it would be desirable to forward other conceptual proposals that could clearly focus on the essential characteristics of micro-development. It is in this context that emerges the proposal of the concept of participative development, in an exploratory analysis that we want to expose to scientific debate.